2022
DOI: 10.3389/fevo.2022.898805
|View full text |Cite
|
Sign up to set email alerts
|

Functional Responses Shape Node and Network Level Properties of a Simplified Boreal Food Web

Abstract: Ecological communities are fundamentally connected through a network of trophic interactions that are often complex and difficult to model. Substantial variation exists in the nature and magnitude of these interactions across various predators and prey and through time. However, the empirical data needed to characterize these relationships are difficult to obtain in natural systems, even for relatively simple food webs. Consequently, prey-dependent relationships and specifically the hyperbolic form (Holling’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…Researchers use functional responses to quantitatively describe the interactions of consumers and resources, including, but not limited to, predator-prey, parasitoid-host, parasitehost, or filter-feeder-plankton interactions. The functional response concept (Solomon, 1949;Holling, 1959a,b) is a cornerstone of population and food-web ecology and is still widely relevant (e.g., DeLong, 2021;Gobin et al, 2022). Solomon (1949) introduced the idea by stating: "…there must be a functional response to (say) an increase in the host density, because of the increased availability of victims: as host density rises, each enemy will attack more host individuals,…".…”
Section: Introduction 1what Are Functional Responses?mentioning
confidence: 99%
“…Researchers use functional responses to quantitatively describe the interactions of consumers and resources, including, but not limited to, predator-prey, parasitoid-host, parasitehost, or filter-feeder-plankton interactions. The functional response concept (Solomon, 1949;Holling, 1959a,b) is a cornerstone of population and food-web ecology and is still widely relevant (e.g., DeLong, 2021;Gobin et al, 2022). Solomon (1949) introduced the idea by stating: "…there must be a functional response to (say) an increase in the host density, because of the increased availability of victims: as host density rises, each enemy will attack more host individuals,…".…”
Section: Introduction 1what Are Functional Responses?mentioning
confidence: 99%
“…In this paper, we use three basic forms of the functional response as simple heuristics for conservation managers: linear (called a Type I), asymptotic or saturating (Type II), and sigmoidal (Type III) where a predator's food intake increases slowly at first and then asymptotes (see Figure 2.1 in DeLong, 2021). The ecology of functional responses is far more complex than these simple depictions given the influence of factors other than the density of the focal prey, such as the density of alternative prey, food caching, surplus killing, diet switching and predator interference (e.g., Abrams, 2022; DeLong, 2021; Gobin et al, 2022; Krebs, 2022). These complexities are not considered here.…”
Section: A Precis Of Numerical and Functional Responses And Prey Recr...mentioning
confidence: 99%
“…Recent empirical work has suggested that a variety of different interference effects occur between different mammalian top predators (Engebretsen et al, 2021). Gobin et al (2022) discuss several modifications of type II responses in the context of models of a relatively well-studied boreal system in which five vertebrate species were represented. They analyze food web properties of best-fit models with different functional response forms, and conclude that type II responses produce relative poor fits to observed population and food web data.…”
Section: Adaptively Flexible Functional Responses In Models With Threementioning
confidence: 99%